FPGA based LCD for Flood Monitoring Warning System / Mohamad Afiq Azman - Azman, Mohamad Afiq (2012)
Monsoon floods and flash floods are the most severe climate-related natural disaster in Malaysia. Although the Department of Irrigation and Drainage Malaysia has provided online information on flooded areas and highways, there is still no alarm signal if flash flood occurs. Flood Monitoring Warning System (FMWS) with FPGA (Field Programmable Gate Array) based is expected to be an inexpensive system which can provide information based on the water and water flow detecting system. The information can be read from the system display. This report explains the configuration and programming technique for displaying information on different type of LCD using Altera DE2 Development Board. The LCDs has been tested and found to be able to display the expected graph and picture based on the condition of the water level and flowrate.